2022
DOI: 10.1002/adma.202106945
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Strategies for Plant Genetic Engineering

Abstract: Plant genetic engineering is essential for improving crop yield, quality, and resistance to abiotic/biotic stresses for sustainable agriculture. Agrobacterium‐, biolistic bombardment‐, electroporation‐, and poly(ethylene glycol) (PEG)‐mediated genetic‐transformation systems are extensively used in plant genetic engineering. However, these systems have limitations, including species dependency, destruction of plant tissues, low transformation efficiency, and high cost. Recently, nanotechnology‐based gene‐delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 221 publications
0
54
0
Order By: Relevance
“…Our biosensor can be used for the future development of plant sensors for monitoring plant signaling pathways and metabolism that are nondestructive, minimally invasive, and capable of real-time, in situ analysis. It can be translated to crop plant species for agriculture applications. , However, there will be many challenges for plant biosensors in field conditions . Large-scale field demonstrations under agricultural conditions are critically needed to understand biosensors’ feasibility and limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our biosensor can be used for the future development of plant sensors for monitoring plant signaling pathways and metabolism that are nondestructive, minimally invasive, and capable of real-time, in situ analysis. It can be translated to crop plant species for agriculture applications. , However, there will be many challenges for plant biosensors in field conditions . Large-scale field demonstrations under agricultural conditions are critically needed to understand biosensors’ feasibility and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It can be translated to crop plant species for agriculture applications. 66,67 However, there will be many challenges for plant biosensors in field conditions. 68 Large-scale field demonstrations under agricultural conditions are critically needed to understand biosensors' feasibility and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that tools such as carbon nanotubes and the widely used CRISPR-Cas9 genetic editing might be used to efficiently change the plant's genetic material (Demirer et al, 2021). A wide variety of crops have been successfully modified using the CRISPR/Cas technique due to its precision, simplicity, and low cost (Mandal et al, 2022;Yan et al, 2022). Nanomaterialmediated gene editing now provides the benefits of species independence, ease of use, acceptable preservation of external nucleic acids, strong biocompatibility, high transformation efficiency, and the potential for plant regeneration (He et al, 2019).…”
Section: Metabolism and Signal Transduction Of Cytokininsmentioning
confidence: 99%
“…Hortelão et al constructed LipoBots composed of a liposomal carrier containing urease enzymes for propulsion . We reason that the dynamic organization of catalytic NPs may also be effective. , A fluid liposomal surface may provide an attractive platform to test this hypothesis. , Moreover, understanding the interaction between NPs and phospholipid membranes impacts the development of biophysics, medicine, plant science, and nanobiotechnology. A lot of simulation and experimental work have revealed the effect of particle types, size, charge, shape, and surface chemistry on the interaction with phospholipid membranes. Nevertheless, to the best of our knowledge, although individual nanoparticles associating with each other spontaneously into a defined and organized structure has been widely explored, manipulating the assembly of NPs on lipid membranes is still challenging. Previous studies reported that fluid-phase liposomes could promote the aggregation of citrate-capped gold NPs (cit-Au), providing another way to manipulate NP assembly on fluid-phase lipid surfaces. Ma et al controlled the assembly of cit-Au on fluid-phase liposomes, providing a practical approach for deep tissue immunogenic cell death cancer immunotherapy with hybrids’ near-infrared II optical absorption property …”
Section: Introductionmentioning
confidence: 99%